Analyser les formules pragmatiques de la conversation : problèmes de méthodes dans une perspective lexicographique - Grossmann, Francis; Krzyżanowska, Anna (Neophilologica, 2020)
Through some examples, the paper illustrates the lexicographic approach implemented in the Polonium PRAGMALEX project, which aims to provide a pragma-semantic description of conversational formulas in French with their equivalent in Polish and Italian, highlighting their pragmatic values. The sociolinguistic or cultural factors that determine their use in the discourse are also made more explicit.